Scale Mixture of Gaussian Modelling of Polarimetric SAR Data. (16th November 2009) - Doulgeris Doulgeris, Anthony P. Anthony P.; Eltoft Eltoft, Torbjørn Torbjørn
Abstract : This paper describes a flexible non-Gaussian statistical method used to model polarimetric synthetic aperture radar (POLSAR) data. We outline the theoretical basis of the well-know product model as described by the class of Scale Mixture models and discuss their appropriateness for modelling radar data. The statistical distributions of several Scale mixture models are then described, including the commonly used Gaussian model, and techniques for model parameter estimation are given. Real data evaluations are made using airborne fully polarimetric SAR studies for several distinct land cover types. Generic scale mixture of Gaussian features is extracted from the model parameters and a simple clustering example presented.